Dampak Implementasi Pengintegrasian Kurikulum Terhadap Mutu Pembelajaran: Analisis Kasus MTs Sains Karimiyyah Kebasen - Tia Mugi Winasih; Nur Fuadi (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This research aims to find out how the combination of the Al-Azhar Curriculum with the independent curriculum in an educational institution, especially the impact it has on student intelligence, of course there are several schools that use an integration basis between the two. One of these educational institutions is MTs Ilmu Al-Karimiyyah Kebasen which seeks to discover new innovations in developing new curricula. In this research, a qualitative approach is used, a descriptive type of analysis, which will provide a description of narrative data related to the process of adopting an adaptation model for the integration of the independent curriculum and the Egyptian Al-Azhar curriculum in religious learning activities at MTs Ilmu Al-Karimiyyah Kebasen. The objectives of this research are: a. To analyze how the integration and implementation of the Merdeka curriculum model and the Egyptian Al-Azhar Curriculum are carried out at MTs Ilmu Karamiyyah Kebasen. b. To analyze how to adopt and adapt the two curricula. c) to explain the impact that occurs on students both from inhibiting and supporting factors in implementing the model between the two curricula. The results of this research conclude that the integration model in PAI learning between the Merdeka and Al-Azhar Egyptian curricula takes the form of a merger of the Ministry of Education and Culture and the Ministry of Religion. As well as the supporting factors for this integration, namely the horizontal and vertical coordination of the Kamad and the teachers' council, the Kamad's innovation ideas, the committee in this case completely supports the madrasah in its policy of finding innovation in curriculum development. The inhibiting factor is limited ability to speak Arabic due to limited understanding of language skills and education.